nani7050
nani7050
19-06-2019
Mathematics
contestada
If f(x)= -6x+8, then f^-1(x)=
Respuesta :
AVstudios
AVstudios
19-06-2019
Answer:
I believe it would be x-8/-6
Step-by-step explanation:
y = -6x + 8
x - 8 = -6y
x - 8/-6 = y
Answer Link
VER TODAS LAS RESPUESTAS ( 42+ )
ACCESS MORE
Otras preguntas
how does a diet affect diabetes? calcium helps maintain blood sugar level, and a Diet low in calcium contribute to diabetes, a diet high in sugar and fat can le
What was the effect of the reform act of 1832?
The equation below is for potassium oxide. 4K + O2 → 2K2O The ratio of atoms of potassium to ratio of atoms of oxygen is BLANK
I need help with question 6-8
Coal, oil and natural gas are all classified as what type of resource? A) Consumable B) Nonrenewable C) Potential D) Renewable
What is the difference between active and passive immunity
Please help on this sorry I have tryed
one result of the wars of religion was that the power of religious authorities like the pope was
Y=-2/3x^2 State the following Domain Range Vertex Axis of symmetry Vertex minimum/maximum Is y=-2/3x^2 wider or narrower than y=x^2 Cant use a calc
What is the function of meiosis?